Management Fisioterapi untuk Penanganan Stifness Knee Et Causa Fraktur Tibia 1/3 Distal : Case Report - Tasya Ghea Amanda; Totok Budi Santoso; Kingkinnarti Kingkinnarti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Knee stiffness is one of the most common complications experienced by patients with tibial fractures. It can weaken and limit accessory joint movement, inhibit muscle activation, impair gait pattern, and reduce the overall physiological range of motion. Surgical procedures may also affect functional capacity and decrease quality of life due to limitations in the patient's activities of daily living (ADL).This case report aims to explore the management and effectiveness of physiotherapy interventions in a case of knee stiffness. A single-subject research design was used to observe a patient, Mr. JP, aged 53 years, who complained of stiffness, pain, and muscle weakness in the left knee (genu sinistra) following trauma. The study was conducted in February 2025. Physiotherapy sessions were carried out every three days, for a total of four sessions. Interventions included Infrared therapy, Transcutaneous Electrical Nerve Stimulation (TENS), and exercise therapy in the form of passive forced exercises, hold-relax techniques, and active resisted exercises.Progress was observed from session T1 to T4, assessed through various parameters: pain levels measured by the Numerical Rating Scale (NRS), muscle strength evaluated using Manual Muscle Testing (MMT), range of motion (ROM) assessed with a goniometer, and functional ability measured using the International Knee Documentation Committee (IKDC) questionnaire. The physiotherapy intervention using Infrared, TENS, and therapeutic exercises (passive forced, hold-relax, and active resisted) showed improvements in reducing pain, increasing muscle strength, enhancing joint ROM, and improving ADL performance in a patient with post-tibial fracture knee stiffness.